American Film Industry: Shaping Global Perceptions? - Chen, Jia (International Journal of Social Sciences and Public Administration, 2024)
The hegemony of the United States extends its influence across the globe, shaping political, economic, and cultural landscapes. Americanization and imperialism have propelled American culture worldwide, with Hollywood movies serving as a significant tool of cultural dissemination. The economic dominance of the U.S. in the film industry plays a pivotal role in shaping global perceptions of the country. This article delves into the mechanisms through which Americanization and imperialism exert control over the film industry to promote their cultural narratives. Furthermore, by examining the perspectives of various scholars, this article concludes that while the U.S. wields significant influence over the film industry through imperialism, it may not fundamentally alter international perceptions of the nation.